Isolamento e caracterização de microssatélites em Aegla longirostri (Crustacea, Decapoda, Anomura) - Roratto, Paula Angélica (2007)
Aeglidae is the only freshwater anomuran family. Fossil evidences relate a marine origin for aeglids. However, genus Aegla invaded the freshwater environment of southern South America, becoming endemic and widespread in that Neotropical region. Besides, the group is widely diversified, consisting of approximately 70 recognized species. Despite the species richness, aeglids have experienced progressive habitat loss and reduction in their populations due to the steam environments alterations. In order to enable future works on Aegla diversity, this study proposed to develop microsatellite markers for Aegla longirostri. Because of their high polymorphism, such molecular markers have been widely used for establishing genetic structure, dynamic and relationship within and among populations. A total of 42 true microsatellite loci was isolated from the library enriched for (CA)n repeats, besides 17 chimeric sequences attained from technical artifacts. The repeats ranged from 3 to more than forty units. However, primer pairs could be developed for thirteen sequences. Successful PCR amplifications were obtained for loci AlCA135 and AlGA138 up to the moment. This microsatellite loci have been screening in 15 individuals of a population from the central region of Rio Grande do Sul State, Brazil, where that species is endemic, in order to evaluate polymorphism. The other developed primer pairs are still undergoing optimization. These markers are promising for investigating population genetic structure for this species. Besides, they revealed cross-species amplification when tested with Aegla uruguayana. Chimeric PCR products attained in this study, which correspond to 29% of the captured sequences, were object of a deep study about artifacts in microsatellite isolation. Moreover, it was proposed a mechanism to explain their formation and implications.